2013
DOI: 10.1016/j.fct.2013.06.054
|View full text |Cite
|
Sign up to set email alerts
|

Fatty acid profile, oxidative stability and toxicological safety of bayberry kernel oil

Abstract: The fatty acid profile, oxidative stability and toxicological safety of bayberry (Myrica rubra Sieb. et Zucc.) kernel oil (BKO) extracted by supercritical carbon dioxide (SC-CO₂) and solvent of diethyl ether were assessed. Fatty acid profile was determined by gas chromatography, oxidative stability by placing the sample of 25g in a blast oven at 50±1°C to accelerate oxidation and toxicological safety by bacterial reverse mutation (Ames test) and acute oral toxicity in mice. The results demonstrated that in com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 17 publications
2
6
0
Order By: Relevance
“…(2008) compared the effect of SE, EAE and ESE on goldenberry seed oil and observed that the extraction techniques did not significantly affect the general profile of fatty acids. Similar observations were reported by Xia et al. (2013) on bayberry seed oil from solvent and SC-CO 2 extraction.…”
Section: Processing Factors Affecting Quality Attributes Of Edible Frsupporting
confidence: 90%
See 1 more Smart Citation
“…(2008) compared the effect of SE, EAE and ESE on goldenberry seed oil and observed that the extraction techniques did not significantly affect the general profile of fatty acids. Similar observations were reported by Xia et al. (2013) on bayberry seed oil from solvent and SC-CO 2 extraction.…”
Section: Processing Factors Affecting Quality Attributes Of Edible Frsupporting
confidence: 90%
“…(2018) Bayberry Super critical CO 2 (SC–CO 2 ), solvent (hexane) extraction (SE) The fatty acids were not considerably different. Xia et al. (2013) Raspberry Ultrasonic-assisted extraction (UAE), solvent extraction (SE) Higher stearic acid and SFA were shown by SE oil.…”
Section: Processing Factors Affecting Quality Attributes Of Edible Frmentioning
confidence: 99%
“…is native to eastern Asia, mainly China, and it is very popular with the local consumers because of its sweet/sour taste, flavor, and color. [1,2] All parts of the bayberry plant are used in Chinese traditional medicines. [3] Bayberries are an important source of phytochemicals, such as phenolic acids, anthocyanins, and flavonol glycosides.…”
Section: Introductionmentioning
confidence: 99%
“…As shown in Table 4, Mudong bayberry oil is very abundant in unsaturated fatty acids, with a content of 86%, which is close to the unsaturated fatty acids content in Jiangxi wild bayberry oil (86%), Zhejiang Biqi bayberry oil (84%), Zhejiang Shui bayberry oil (85%), olive oil (80%), and camellia oil (90%) (Xia et al, 2013, Allalout et al, 2009). The proportion of oleic acid (47%) and linoleic acid (37%) in Mudong bayberry oil was close to that found in Zhejiang Biqi bayberry oil and Zhejiang Shui bayberry oil (Xia et al, 2013). In addition, a small amount of linolenic acid (0.12%) was detected.…”
Section: Fatty Acid Composition Of Kernel Oilmentioning
confidence: 99%
“…According to previous reports, bayberry kernels contain high levels of oil (58.12-70.79%) (Cheng et al, 2009). Unsaturated fatty acids account for more than 85% of total fatty acids found in bayberry kernels (Zhang et al, 2012);, in which the contents of oleic acid and linoleic acid reach up to 40% and the content of linolenic acid is 0.1% (Xia et al, 2013, Cheng et al, 2008. Linoleic acid plays an important physiological role in reducing hypertension, hyperglycemia, and hyperlipidemia, as well as preventing fatty liver and atherosclerosis (Bhattacharya et al, 2006, Yurawecz et al, 1999.…”
Section: Introductionmentioning
confidence: 99%